Pengaruh Model Penerimaan Teknologi dan Literasi Keuangan Syariah terhadap Niat Transaksi Zakat, Infaq, dan Sedekah (ZIS) Berbasis Digital (Studi Kasus Jabodetabek) - Tatial Maulida Putri; Sebastian Herman (Institut Syekh Abdul Halim Hasan Binjai, 2022)
This Thesis Discusses the Effect of Technology Acceptance Model (TAM) and Sharia Financial Literacy of Intention Digital Based ZIS Transactions. This study uses a quantitative approach through the SEM-PLS method by taking a case study in Jabodetabek area. The data from this study were obtained from the results of distributing questionnaires to respondents, moeslim and use Fin-Tech for ZIS Transactions. The results showed that of the 6 hypotheses, there were 4 accepted hypotheses, namely 1) perception had a significant effect on attitude 2) perceived ease of use had a significant effect on attitudes 3) perceived ease of use had a significant effect on perceived use 4) attitude had a significant effect on transaction intentions. On the other hand, Islamic financial literacy has no significant effect on attitudes and transaction intentions